Analisis Analisis Kelayakan Dan Persepsi Pengunjung Terhadap Obyek Dan Daya Tarik Wisata Alam (ODTWA) Pantai Lon Malang - Triana Setiyarini; Yustina Chrismardani (Faculty of Economics and Business, University of Pancasakti Tegal, 2024)
The aim of the study was to determine the level of feasibility and visitors' perceptions of Natural Tourism Objects and Attractions (ODTWA) Lon Malang Beach, Sampang Regency. The research method uses descriptive quantitative because it describes a condition of feasibility level and visitors' perceptions objectively based on numbers. The data collection method was carried out through interviews with 3 informants to obtain information regarding the feasibility of ODTWA and questionnaires to obtain data on visitor perceptions. The sample for the purpose of analyzing visitor perceptions is 100 respondents. The results of the study indicate that Lon Malang Beach is feasible to be developed as a tourist destination. On average, ODTWA received a